Hello Ruby. Journey inside the computer - Liukas, Linda (Feiwel and Friends, 2017)
In Ruby's world anything is possible if you put your mind to it even fixing her father's broken computer! Join Ruby and her new friend, Mouse, on an imaginative journey through the insides of a computer in search of the missing Cursor.